Belize environment outlook : GEO Belize 2010 (The Department BelmopanBZ, 2010)
Uses UNEP's methodology for Integrated Environmental Assessment (IEA), known as GEO methodology. Describes the environmental state and trends but also analyses the root causes of such situations and their impacts, looking at the effectiveness of policy actions already in place, and suggesting specific areas for consideration of decision and policy-makers.
References: p. 141-148.